-7y-14+2y+6=6y+11

Add -7y and 2y.

-5y-14+6=6y+11

Add -14 and 6.

-5y-8=6y+11

-5y-8=6y+11

Subtract 6y from both sides of the equation.

-5y-8-6y=11

Subtract 6y from -5y.

-11y-8=11

-11y-8=11

Add 8 to both sides of the equation.

-11y=11+8

Add 11 and 8.

-11y=19

-11y=19

Divide each term in -11y=19 by -11.

-11y-11=19-11

Cancel the common factor of -11.

Cancel the common factor.

-11y-11=19-11

Divide y by 1.

y=19-11

y=19-11

Move the negative in front of the fraction.

y=-1911

y=-1911

The result can be shown in multiple forms.

Exact Form:

y=-1911

Decimal Form:

y=-1.72‾

Mixed Number Form:

y=-1811

Solve for y -7y-14+2y+6=6y+11